Analysis Of Suffixed Words of Plywood Manufacturing Article - Jumanto Jumanto; Eugene Chung; Florence Hadi Soeroyo Oei; Misbachul Munir Al Fattah (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2024)
The purpose of this research to find out and analyze suffix word of the manufacturing process. The primary goal of this research is to determine how the suffixing process occurs in the manufacturing plywood. Plywood stands as a foundational building material, comprising thin wood layers or plies bonded together with adhesive. It divides into two primary categories: softwood plywood and hardwood plywood, each aligning with specific tree species. Coniferous varieties, such as firs and pines, predominantly contribute to softwood plywood, while deciduous species, including oak, poplar, maple, cherry, and larch, find prominence in hardwood plywood. Softwood plywood undergoes production by bonding multiple layers of dry softwood veneers with adhesive. Its versatile applications encompass wall siding, sheathing, roof decking, concrete formboards, floors, and containers. Within industrial classifications, it falls under Standard Industrial Classification (SIC) code 2436 and North American Industrial Classification System (NAICS) code 321212 for "Softwood Plywood and Veneer." On the other hand, hardwood plywood emerges from the bonding of hardwood veneers using adhesive. The face and back layers encase a core, typically composed of lumber, veneer, particleboard, or medium density fiberboard. Hardwood plywood manifests in various forms, from panels to specialized components like curved hardwood plywood, seat backs, and chair arms. Its domain of application extends to interior uses such as furniture, cabinets, architectural millwork, paneling, flooring, store fixtures, and doors. Classified under SIC code 2435 and NAICS code 321211 for "Hardwood Plywood and Veneer," this type of plywood showcases a distinct production process.